A carbon-wrapped nanoscaled thermometer for temperature control in biological environments. (June 2008) - Vyalikh, Anastasia; Wolter, Anja UB; Hampel, Silke; Haase, Diana; Ritschel, Manfred; Leonhardt, Albrecht; Grafe, Hans-Joachim; Taylor, Arthur; Kräämer, Kai; Büüchner, Bernd; Klingeler, Rüüdiger
Aims: A carbon-wrapped nanoscaled thermometer for a contactless temperature control in biological systems on the cellular level is presented.Materials & methods: The thermometer is based on multiwalled carbon nanotubes (MWCNTs) filled with materials with strongly temperature-dependent nuclear magnetic resonance (NMR) parameters. The NMR frequency shift and relaxation time were measured in cuprous-iodide-filled CNTs at different temperatures.Results: The experimental data indicate a pronounced temperature dependence of the NMR parameters, thereby realizing the nanoscaled thermometer.Conclusion: This study is a proof-of-concept that the functionalized CNTs can be used as a contactless thermometer in biomedical applications.